Assessing the Impact of Prime Age Composition and Biological Asset Intensity on Sustainable Growth: In Indonesia Agriculture Case - Suhardjo, Iwan; Meiliana, Meiliana; Justin, Justin; Phang, Serena; Cuandra, Aurelia Priscilla; Agustinus, Viandi (Universitas Galuh, 2024)
The study aims to examine the levels of sustainable growth influenced by the global climate, the prime age composition, the intensity of biological assets, and the certification of agricultural industry in Indonesia, which will provide an overview of the sensitivity of each factor to sustainable growth in the Company that will help in the development of the Company's future performance strategies that are synergistic with sustainability. The measurement method used in this study is the experimental quantitative method. The selection of samples for this study is based on the criteria that have been determined with the number of samples as many as 11 agricultural companies listed on the Indonesian Stock Exchange (BEI). The results of the research conducted are the prime age composition, biological asset intensity, global climate change that moderates the composition of prime age and biological asset intensity, and plantation certification that moderates biological asset intensity has no significant effect on sustainable growth. Whereas certification that moderates the prime age composition has a significantly negative effect on the level of sustainable growth, this is due to the higher costs of demanding certification requirements. Other reasons that explain the variable's lack of effect are the influence of efficiency levels and management strategies, environmental development strategies of agricultural practices, and management factors which are believed to be more influential than the independent variables studied.